THE DEVELOPMENT OF AN AUTHENTHIC INSTRUMENT FOR TO THE MATTER ENVIRONMENTAL CHANGES CLASS X HIGH SCHOOL IN ORDER TO STUDY RESULTS STUDENTS - Emilia Elis Hartanti; Sifak Indana (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
The research aimed to identify the validity, practicality, and readability of authentic assessment instruments. The research is based on the model of research development research development research and development (R & D) consisting of six steps and potential, the collection of information, product design, validation of the product design, the revision of the product design, the limited test. To collect the data held in SMAN 1 Cerme on August involving as many 16 students of XI heterogeneous. Data collection method uses the validation and methods of observation. An analysis of the results of the data analysis using instrumen validation, the analysis of the activity of students, an analysis of the performance/practices, the student responded, and readability analysis. Based on the research done show results validation an instrument assessment seen from domain the contents with the feasibility 86.67%. Seen from domain construction with the feasibility 83.3%. In domain language after dipersentase its feasibility of 87.5%. Based on the results of the recapitulation of the activity of students who have been carried out by an observer it can be seen that the activity of students achieved a score of with the percentage 96.8 % or it can be said very practical. On the outcome of an instrument authentic assessment readability have a score with the level of 10 from 5 samples have been taken. Based on the analysis of the data can be inferred that the aspect of the criteria for validation in the category of very good/ perfectly valid, and based on the aspect of practicality in the category of very practical, and from the perspective of readabilityt the same level in the category of 10 so that equivalent to class X high school.Key word : Authenthic Assessment, Enviromental Changes, 2013 Curriculum.